Human papillomavirus positivity and cervical lesions in relation to HIV infection: a comparative assessment in the Cameroonian female population - Samuel M. Sosso; Michel C.T. Tchouaket; Joseph Fokam; Rachel K. Simo; Ezechiel N.J. Semengue; Zacharie Sando; Judith Torimiro; Aline Tiga; Elise E. Lobe; Georgia Ambada; Achille Nange; Alex D. Nka; et al. (AOSIS, 2023)
Cervical lesions, induced by high-risk oncogenic human papillomavirus (HR-HPV), in the context of HIV remains a global health challenge. We determined the effect of HR-HPV on the development of cervical lesions in women with and without HIV infection. A cross-sectional analytical study was conducted among 257 women living in Cameroon. HIV serology, HR-HPV genotyping and cervico-vaginal smear (CVS) were performed for all participants; among those declared HIV positive, plasma HIV viral load and CD4 count were measured. Statistical analyses were performed using Graph Pad version 6.0; P0.05 was considered statistically significant. The mean age of the participants in our study was 37±6.5 years. According to HIV serology, 184 (71.59%) were HIV‑positive vs. 73 (28.40%) HIV‑negative. Among the HIV‑positive women, the median CD4 count was 438 [IQR: 317‑597] cells/mm3 and the median viremia was 40 [IQR:40‑2318] copies/ml. After successful genotyping, the prevalence of HR‑HPV was 36.32% (73/201), with a significantly higher proportion in HIV‑infected individuals (41.98% (55/131) vs. 25.71% (18/70); P=0.02; OR=2.1). The overall rate of cervical lesions was 23.34% (60/257), with a non‑significantly higher proportion in HIV‑infected participants (25.00%(46/184) vs. 19.17% (14/73); P=0.31). Relevantly, the presence of HR‑HPV was significantly associated with cervical lesions (P0.0001; OR=5.07), with a higher odds of cervical lesion in HIV‑positive individuals (P0.0001 and OR=5.67) compared to HIV‑negative individuals (P=0.03 and OR=3.83). Although oncogenic HPV appears to be an independent factor in the development of cervical lesions, this study reveals higher odds of cervical lesions among HIV/HPV co-infection than in HPV infection alone.